What to Do with the New Antibiotics? - Khalil Chaïbi; Françoise Jaureguy; Hermann Do Rego; Pablo Ruiz; Céline Mory; Najoua El Helali; Sara Mrabet; Assaf Mizrahi; Jean-Ralph Zahar; Benoît Pilmis (MDPI AG, 2023)
Multidrug-resistant Gram-negative bacteria-related infections have become a real public health problem and have exposed the risk of a therapeutic impasse. In recent years, many new antibiotics have been introduced to enrich the therapeutic armamentarium. Among these new molecules, some are mainly of interest for the treatment of the multidrug-resistant infections associated with Pseudomonas aeruginosa (ceftolozane/tazobactam and imipenem/relebactam); others are for carbapenem-resistant infections associated with Enterobacterales (ceftazidime/avibactam, meropenem/vaborbactam); and finally, there are others that are effective on the majority of multidrug-resistant Gram-negative bacilli (cefiderocol). Most international guidelines recommend these new antibiotics in the treatment of microbiologically documented infections. However, given the significant morbidity and mortality of these infections, particularly in the case of inadequate therapy, it is important to consider the place of these antibiotics in probabilistic treatment. Knowledge of the risk factors for multidrug-resistant Gram-negative bacilli (local ecology, prior colonization, failure of prior antibiotic therapy, and source of infection) seems necessary in order to optimize antibiotic prescriptions. In this review, we will assess these different antibiotics according to the epidemiological data.